Measuring halal brand association (HalBA) for Islamic banks - Maulan, Suharni; Omar, Nor Asiah; Ahmad, Maisarah (Emerald Group Publishing Ltd., 2016)
Purpose: The main purpose of this paper is to develop a reliable and valid scale for measuring halal brand association (HalBA) for Islamic banks. Brand association is a core dimension of brand equity that Islamic bank managers need to develop to maintain competitiveness. Using the process proposed by Churchill for developing measures of marketing constructs, an instrument to assess HalBA for Islamic bank is formulated. Design/methodology/approach: The methodology consists of developing the scale based on a literature review and qualitative method. The proposed scale is then purified and validated through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Findings: Based on the EFA and CFA, the result reveals that HalBA for Islamic banks contains 15 attributes which can be categorized into three dimensions: Shari’ah-compliant association, God-consciousness association and corporate social responsibility association. Practical implications: The scale developed could assist practitioners in further understanding the dimensions and measurement of halal bank association, particularly in Islamic banking institutions. Knowledge of the dimensions of HalBA that customers seek from an Islamic bank can help managers and marketers to design branding strategies that better meet the needs of consumers, thereby increasing their satisfaction and loyalty. Originality/value: The concept of brand association has been explored primarily from a conventional marketing perspective. This study offers a new dimension of HalBA in the context of Islamic banks.